Strategi Pemasaran Pendidikan Berbasis Madrasah Riset dalam Peningkatan Mutu Pendidikan di MAN 1 Ngawi - Roni Harsoyo; Aprilia Dian Sukmawati (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2023)
Improving the quality of educational institutions requires several precise strategies so that the quality can increase significantly, which has an impact on the existence of these educational institutions. One of the strategies is education marketing, which aims to produce quality educational inputs, outputs, and outcomes. MAN 1 Ngawi is one of the madrasas that has implemented a very effective marketing strategy to improve the quality of its education. The results showed that the madrasah research program was one of the activities highlighted by MAN 1 Ngawi as an activity to hone students' mindsets and interests in scientific research to produce new works and innovations that would benefit society and the development of science. Through this research madrasa program, MAN 1 Ngawi can improve the quality of madrasas and provide achievement indicators for its students, who are growing rapidly both at the district level and at the international level. Through this program, it is also hoped that it will be one of the surefire ways to attract the interest of prospective student guardians so that it can significantly increase student input.